Emotional Freedom Technique in School-Based Group Counseling: A Strategy to Reduce Mathematics Anxiety - Putra Suharnadi; Zadrian Ardi; Elvia Kurniawati (AL-ISHLAH: Jurnal Pendidikan, 2026)
Mathematics anxiety is a prevalent emotional barrier that negatively affects students’ academic performance, motivation, and engagement in mathematics learning. School counselors play a crucial role in addressing this issue through effective and evidence-based interventions. Emotional Freedom Technique (EFT), an integrative counseling approach combining cognitive, emotional, and somatic components, has shown promise in reducing anxiety; however, empirical evidence within school-based group counseling contexts remains limited. This study employed a quasi-experimental non-equivalent pretest–posttest control group design to examine the effectiveness of EFT-based group counseling in reducing mathematics anxiety among high school students in Indonesia. Nineteen students with moderate to high levels of mathematics anxiety were selected through purposive sampling and assigned to an experimental group (n = 9) and a control group (n = 10). The experimental group participated in six weekly EFT-based group counseling sessions, while the control group received no specialized intervention. Mathematics anxiety was measured using an adapted Mathematics Anxiety Scale. Data were analyzed using the Wilcoxon Signed-Rank Test and the Mann–Whitney U Test. The results indicated a statistically significant reduction in mathematics anxiety in the experimental group following the intervention (p 0.05), whereas no significant change was observed in the control group. Posttest comparisons revealed a significant difference between the two groups, favoring the experimental group. These findings suggest that EFT-based group counseling is a potentially effective intervention for reducing mathematics anxiety among high school students. Further research with larger samples, randomized designs, and longitudinal follow-up is recommended to strengthen the evidence base and generalizability of the findings.